Common Cold - Eccles, Ronald; Weber, Olaf (Birkhäuser Advances in Infectious Diseases, 2009)
The common cold is unlike any other human disease. It seems impossible to defeat and affects all of us on a regular basis. Due to the large number of viruses causing colds any specific cure is a major challenge. This unique book brings together a wide range of topics, from our ancestors' views about disease, followed by the questions why and how we sneeze, cough and get a runny nose, to the intricacies of host-virus interactions and immunological phenomena on the molecular level. Popular treatments, "over the counter" medicines and interventions are reviewed. Finally recent developments and new treatment options are highlighted.